MYC drives overexpression of telomerase RNA (hTR/TERC) in prostate cancer. Issue 1 (14th November 2017) - Baena‐Del Valle, Javier A; Zheng, Qizhi; Esopi, David M; Rubenstein, Michael; Hubbard, Gretchen K; Moncaliano, Maria C; Hruszkewycz, Andrew; Vaghasia, Ajay; Yegnasubramanian, Srinivasan; Wheelan, Sarah J; Meeker, Alan K; Heaphy, Christopher M; et al.
Abstract: Telomerase consists of at least two essential elements, an RNA component hTR or TERC that contains the template for telomere DNA addition and a catalytic reverse transcriptase (TERT). While expression of TERT has been considered the key rate‐limiting component for telomerase activity, increasing evidence suggests an important role for the regulation of TERC in telomere maintenance and perhaps other functions in human cancer. By using three orthogonal methods including RNAseq, RT‐qPCR, and an analytically validated chromogenic RNA in situ hybridization assay, we report consistent overexpression of TERC in prostate cancer. This overexpression occurs at the precursor stage (e.g. high‐grade prostatic intraepithelial neoplasia or PIN) and persists throughout all stages of disease progression. Levels of TERC correlate with levels of MYC (a known driver of prostate cancer) in clinical samples and we also show the following: forced reductions of MYC result in decreased TERC levels in eight cancer cell lines (prostate, lung, breast, and colorectal); forced overexpression of MYC in PCa cell lines, and in the mouse prostate, results in increased TERC levels; human TERC promoter activity is decreased after MYC silencing; and MYC occupies the TERC locus as assessed by chromatin immunoprecipitation (ChIP). Finally, we show that knockdown of TERC by siRNA results in reduced proliferation of prostate cancer cell lines. These studies indicate that TERC is consistently overexpressed in all stages of prostatic adenocarcinoma and that its expression is regulated by MYC. These findings nominate TERC as a novel prostate cancer biomarker and therapeutic target. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.